Frontispiece: Ultra‐Fast Supercritical Hydrothermal Synthesis of Tobermorite under Thermodynamically Metastable Conditions. Issue 12 (10th March 2017) - Diez‐Garcia, Marta; Gaitero, Juan J.; Dolado, Jorge S.; Aymonier, Cyril
Abstract : Mineral Synthesis The durability of buildings—from Roman to modern ones—is partly due to the mineral tobermorite which is used in cement. In their Communication onpage 3162 ff., J. J. Gaitero, C. Aymonier et al. report how tobermorite can be synthesized in seconds.